The experience of financial toxicity among advanced melanoma patients treated with immunotherapy. Issue 2 (4th March 2021) - Thom, Bridgette; Mamoor, Maha; Lavery, Jessica A.; Baxi, Shrujal S.; Khan, Niloufer; Rogak, Lauren J.; Sidlow, Robert; Korenstein, Deborah
Abstract: Purpose To measure financial toxicity and explore its association with quality of life (QOL) in an emerging population of survivors: advanced melanoma patients treated with immunotherapy. Design Cross-sectional survey and medical record review. Sample 106 survivors (39% response). Median time since start of immunotherapy was 36.4 months (range: 14.2–133.9). Methods The Comprehensive Score for Financial Toxicity measured financial toxicity, and the EORTC-QLQ30 assessed QOL and functioning across five domains. Data were collected online, by phone, or in clinic. Findings : Younger patients (<65 years) reported higher financial toxicity ( p < .001) than older patients. Controlling for age, financial toxicity was correlated with QOL ( p < .001), financial difficulties ( p < .001), and EORTC-QLQ30 functioning subscales. Conclusions Given the demonstrated association between financial toxicity and QOL, our study highlights the importance of addressing financial toxicity, particularly among patients receiving high-cost treatments. Implications for Psychosocial Providers : Providers should educate patients and their caregivers about cost-management techniques, link them with available resources, and provide psychosocial counseling to alleviate related distress.